Causes of embryo implantation failure: A systematic review and metaanalysis of procedures to increase embryo implantation potential - Bulletti, Francesco M.; Sciorio, Romualdo; Conforti, Alessandro; De Luca, Roberto; Bulletti, Carlo; Palagiano, Antonio; Berrettini, Marco; Scaravelli, Giulia; Pierson, Roger A. (Frontiers in Endocrinology, 2025)
IntroductionInfertility is characterized by the failure to conceive after 12 months of unprotected sexual intercourse. In assisted reproduction technologies (ARTs), in-vitro fertilization and embryo transfer (IVF-ET) are pivotal, with the quality of embryo quality essential for successful implantation.ObjectiveThis systematic review with meta-analysis aimed to explore the prevalence of embryonic factors involved in the implantation process, concentrating on the following research inquiries: 1) the implantation rates of euploid versus untested embryo transfers; 2) the efficiency of transferring good embryos in different age groups; 3) the impact of age on good embryo transfers to gestational carriers; and 4) the transfer of donated gametes/embryos. The goal is to identify critical points in implantation to improve therapies.MethodsA comprehensive literature search identified 1474 relevant papers, 11 of which met the inclusion criteria. The information was gathered using a standardized form, and the risk of bias was evaluated. A meta-analysis of subgroups to determine euploid embryo transfer efficiency was conducted to synthesize and explore the results. Furthermore, data extracted from registries document the persistent secondary role of extraembryonic determinants in successful implantation.ResultsThe meta-analysis demonstrated that preimplantation genetic testing for aneuploidy (PGT-A) significantly increased the odds of implantation. Age was found to influence extraembryonic factors, with older women experiencing reduced embryo implantation as gestational carriers. However, the overall incidence of extraembryonic factors was low. This review highlights the need to focus on PGT-A, diagnostic hysteroscopy, and endometrial receptivity for improving implantation rates.ConclusionImplantation success in ARTs largely depends on embryo euploidy. While achieving three euploid embryos greatly increases success rates, it is challenging in older women. Extraembryonic factors, although present, have a marginal impact. Subsequent studies ought to concentrate on modulating endometrial responses immunologically and developing algorithms to improve the precision of predicting implantation success; as well as the timing of endometrial receptivity and the occurrence of dormant embryo phenomena also warrants further investigation.